Ultrafast dynamics in molecular ions following UV and XUV excitation: a perspective. Issue 1 (31st December 2022) - Hervé, Marius; Boyer, Alexie; Brédy, Richard; Compagnon, Isabelle; Lépine, Franck
ABSTRACT: Gas phase experiments combined with ultrafast technologies can provide information on the intrinsic properties of molecular systems at picosecond, femtosecond, or even attosecond timescales. However, these experiments are often limited to relatively simple model systems. In this context, electrospray ionization sources (ESI) have offered new perspectives as they allow to produce large or fragile molecular ions in the gas phase, mimicking molecules in their natural environment. While time-resolved UV-visible ultrafast experiments on molecular ions have been successfully developed over the past decades, efforts are still required to perform experiments using ultrashort extreme ultraviolet (XUV) pulses with the goal of reaching attosecond resolution. In this article, we present recent results obtained using the combination of ultrafast technologies and ESI sources. We show that ultrafast dynamics experiments can be performed on molecular ions without ion trapping devices and can reveal UV-induced charge transfer in small peptides with controlled micro-environment. Non-adiabatic relaxation dynamics in large (bio)molecular ions is also presented. Such experiments are compatible with high harmonic generation XUV sources as shown here in the case of a metal complex. These ultrafast dynamics studies on large molecular ions offer new perspectives in attosecond science. Graphical abstract: uf0001